Will I stay or will I go? Plant species‐specific response and tolerance to high land‐use intensity in temperate grassland ecosystems. (25th June 2019) - Busch, Verena; Klaus, Valentin H.; Schäfer, Deborah; Prati, Daniel; Boch, Steffen; Müller, Jörg; Chisté, Melanie; Mody, Karsten; Blüthgen, Nico; Fischer, Markus; Hölzel, Norbert; Kleinebecker, Till
Abstract: Aim: Intensification of land use strongly impacts plant communities by causing shifts in taxonomic and functional composition. Mechanisms of land use‐induced biodiversity losses have been described for temperate grasslands, but a quantitative assessment of species‐specific occurrence optima and maximum tolerance (niche breadth) to land‐use intensity (LUI) in Central European grasslands is still lacking. Location: Temperate, managed permanent grasslands in three regions of Germany. Methods: We combined extensive field work with a null model–randomization approach, defined a "habitat niche" for each plant species based on occurrence and abundance across 150 grassland sites differing in LUI (i.e., amount of fertilizer, mowing/grazing intensity and a compound index of these), and assessed their realized niche breadth (tolerance). Underlying mechanisms driving species' responses to LUI were assessed by relating plant functional traits, Ellenberg indicator values (EIV), Grime's ecological strategies (CSR) and Briemle utilization numbers. Results: Out of 151 plant species, 34% responded negatively, whereas 10% responded positively to high LUI. This pattern was mainly driven by species' response to fertilization and mowing frequency; grazing intensity response was less pronounced. Positively reacting species, displaying broader niches, were associated with competition‐related functional traits, high EIV for nutrient supply and moisture and high mowing tolerance under spatiotemporally variable conditions. Negatively responding species, displaying relatively narrow niches confined to spatiotemporally homogeneous low LUI sites, were associated with a nutrient‐retentive strategy, under nutrient‐poor, base‐rich soil conditions. Conclusion: Our analyses of individual species' reactions clearly demonstrate that species responding negatively to high LUI display little tolerance towards intensive fertilization and mowing, leading to plant diversity loss; whereas grazing partly thwarts these effects by creating new habitat niches and promoting ruderal species. Our approach can be applied to other habitat types and biogeographical regions in order to quantify local specific response or tolerance, adding to existing knowledge about local vegetation dynamics. Abstract : Employing a combined null model–randomization approach based on species' occurrence and abundance in temperate grasslands, we calculated plant species‐specific agricultural habitat niches and niche breadths and characterized response‐driving mechanisms by using plant functional and ecological traits. Our approach may be applied to any other habitat type for explaining and predicting community assembly and species coexistence in response to current land‐use practices.